Analisis Potensi Interferensi Sistem LTE Dengan EGSM Di Pita 800 MHz - Muttaqin, Abdul; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
LTE and EGSM frequency spectrum in Indonesia are located on adjacent frequency channel. This could potentially cause interference among the systems. This study focuses on the analysis of potential interference between downlink LTE (LTE base station as an interferer) versus uplink EGSM (EGSM base station as a victim of interference). This interference could potentially lower the quality of the signal reception on the EGSM base station. In this study, interference between LTE and EGSM on 800 MHz frequency band will be analysed by using SEAMCAT simulation software. From the simulation’s results obtained, the interference of both systems is eliminated by adding the guard band. The guard band distance of 4.5 km for URBAN environment and the distance of 5.5 km for SUB URBAN provide the highest C/I ≥ 12 dB, respectively.Key words: LTE, E-GSM, guard band, interference, SEAMCAT.